Computational study of solar furnace system for the application in solar pyrolysis of mixed plastic waste - Ong, Jing Xian (2023)
While several studies on various aspects of the solar furnace system have been conducted, optimization of the simulation has not received much attention. The purpose of this study is to find the optimal resolutions that produce reasonably accurate results. Solar flux distribution maps were obtained using a simulation software, in which the detailed methodology of ray-tracing algorithm is presented. The optimal resolutions found that take into account value and geometrical profile of flux distribution are k1 = 46 × 10⁻³ and k2 = 15 × 10⁻³. In addition, the simulation results are verified and the feasibility of solar furnace for application in solar pyrolysis of mixed plastic waste is demonstrated.